2017
DOI: 10.4049/jimmunol.1600766
|View full text |Cite
|
Sign up to set email alerts
|

P2Y6 Receptor Antagonist MRS2578 Inhibits Neutrophil Activation and Aggregated Neutrophil Extracellular Trap Formation Induced by Gout-Associated Monosodium Urate Crystals

Abstract: Human neutrophils (polymorphonuclear leukocytes [PMNs]) generate inflammatory responses within the joints of gout patients upon encountering monosodium urate (MSU) crystals. Neutrophil extracellular traps (NETs) are found abundantly in the synovial fluid of gout patients. The detailed mechanism of MSU crystal-induced NET formation remains unknown. Our goal was to shed light on possible roles of purinergic signaling and neutrophil migration in mediating NET formation induced by MSU crystals. Interaction of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 122 publications
(215 reference statements)
6
53
0
Order By: Relevance
“…In a recent study performed by Sil et al, we found that PMNs need to attempt to phagocytose MSU crystals in order to perform subsequent NET release and to form aggNETs [23]. PMNs do not really phagocytose MSU crystals since most of the crystals are far longer than PMNs themselves [23]. Our data indicated that only a small fraction of PMNs engaged in attempting MSU crystal phagocytosis but NET-releasing PMNs were all associated with MSU crystals [23].…”
Section: Monosodium Urate Crystals (Msu)mentioning
confidence: 71%
See 4 more Smart Citations
“…In a recent study performed by Sil et al, we found that PMNs need to attempt to phagocytose MSU crystals in order to perform subsequent NET release and to form aggNETs [23]. PMNs do not really phagocytose MSU crystals since most of the crystals are far longer than PMNs themselves [23]. Our data indicated that only a small fraction of PMNs engaged in attempting MSU crystal phagocytosis but NET-releasing PMNs were all associated with MSU crystals [23].…”
Section: Monosodium Urate Crystals (Msu)mentioning
confidence: 71%
“…PMNs do not really phagocytose MSU crystals since most of the crystals are far longer than PMNs themselves [23]. Our data indicated that only a small fraction of PMNs engaged in attempting MSU crystal phagocytosis but NET-releasing PMNs were all associated with MSU crystals [23]. This let us conclude that MSU crystal phagocytosis is a prerequisite for NET formation [23].…”
Section: Monosodium Urate Crystals (Msu)mentioning
confidence: 78%
See 3 more Smart Citations